Production of Trans‐free fats by chemical interesterified blends of palm stearin and sunflower oil. Issue 11 (3rd October 2019) - Farajzadeh Alan, Davood; Naeli, Mohammad Hossein; Naderi, Mehdi; Jafari, Seid Mahdi; Tavakoli, Hamid Reza
Abstract: In this study, production of trans ‐free fats through chemical interesterification of binary blends of palm stearin (PS) and sunflower oil (SFO) and their physicochemical changes after the process was investigated. Analyzed responses included fatty acid and triacylglycerol composition, iodine value, free fatty acid (FFA), soap content, peroxide value (PV), plastic range, slip melting point (SMP), solid fat content (SFC), and oxidative stability along with potential applications of the interesterified fats. Trans fatty acid content of PS/SFO blends was lower than 0.36%. Chemical interesterification increased the FFA and soap content and also decreased PV and oxidative stability index (at 110°C). After the process, SMP and SFC were reduced, also the plastic range transferred to the lower temperatures. All the interesterified blends melted completely at the body temperature, and their SFC was <32%. The melting characteristics of the PS/SFO‐interesterified blends were suitable for many fat‐based products. Abstract : Production of trans‐free fats through chemical interesterification was studied. Transfatty acid content of PS/SFO blends was lower than 0.36%. Chemical interesterification increased the FFA and soap content.